Composite antibacterial material and preparation method thereof, matt finish antibacterial ceramic rock plate and preparation method thereof

By treating activated zinc oxide and alumina at high temperature, it forms a zinc spinel structure and sprayed onto the ceramic rock slab, solving the problem of poor antibacterial effect of matte ceramic rock slabs and achieving efficient and economical preparation of antibacterial ceramic rock slabs.

CN119138432APending Publication Date: 2024-12-17GUANGDONG NEWPEARL CERAMIC GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411181222.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to achieve antibacterial effects on matte ceramic rock slabs. The traditional antibacterial glaze route causes the antibacterial agent to be coated with glaze, which has insufficient antibacterial performance and high cost.

Method used

Compound antibacterial materials are used to form zinc spinel structures by treating activated zinc oxide and alumina at high temperature, sprayed onto the surface of the glaze layer of the ceramic rock slab to ensure the stability and firmness of antibacterial properties, and at the same time reduce the use of antibacterial materials.

Benefits of technology

It achieves good antibacterial properties and wear resistance of matte ceramic rock slabs, reduces the use and cost of antibacterial materials, avoids melt coating of glaze layer, and improves the durability of antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119138432A_ABST
    Figure CN119138432A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of ceramics, and particularly relates to a composite antibacterial material and a preparation method thereof, and a matt finish antibacterial ceramic rock plate and a preparation method thereof. The composite antibacterial material is obtained through high-temperature treatment of activated zinc oxide and activated aluminum oxide, and the matt finish antibacterial ceramic rock plate with the composite antibacterial material on the glaze surface is obtained in a spraying-co-firing mode. The composite antibacterial material has excellent antibacterial performance, can be kept stable at high temperature, can exist on the surface of a matt finish ceramic rock plate glaze layer more firmly and stably in a spraying-co-firing mode, does not affect the matt effect, greatly reduces the use amount of the antibacterial material under the condition of better playing the effect of the antibacterial material, and has the advantages of low cost and low cost. The cost is reduced, and the method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of ceramics, and specifically relates to a composite antibacterial material and a preparation method thereof, a matte antibacterial ceramic rock plate and a preparation method thereof. Background Art

[0002] With the continuous emergence of antibacterial products and the vigorous publicity related to antibacterial products, the concept of antibacterial has gradually become known to people. As a common product in people's daily life, antibacterial ceramic rock panels have also appeared in the shopping lists of many families. From the antibacterial ceramic rock panel products currently released on the market, there are three main routes in the existing technology: 1. Antibacterial glaze route, that is, by adding antibacterial agents to the glaze and firing them together, an antibacterial ceramic rock panel with an antibacterial glaze is obtained; 2. Antibacterial wax water route, that is, by adding antibacterial agents to polishing wax water, the wax water with antibacterial agents is filled into the micropores of the polished ceramic surface, thereby obtaining an antibacterial ceramic rock panel with excellent antibacterial properties; 3. Composite route, that is, antibacterial glaze composite antibacterial wax water route, which plays a role in enhancing the antibacterial effect and further ensuring the antibacterial properties of antibacterial ceramic rock panels. As we all know, ceramic rock slabs can be divided into matte ceramic rock slabs (also called matte ceramic rock slabs), soft light ceramic rock slabs and high gloss ceramic rock slabs according to their glossiness from low to high. Among them, soft light ceramic rock slabs and high gloss ceramic rock slabs have undergone a polishing process on their surfaces, so they can both use the antibacterial wax water route to achieve effective antibacterial effects, while matte ceramic rock slabs do not require a polishing process during their production process, so they can only achieve antibacterial effects through the antibacterial glaze route.

[0003] Ceramic companies generally use the traditional antibacterial glaze route to achieve antibacterial effects on matte ceramic rock slabs. The traditional antibacterial glaze route is to add the antibacterial agent directly to the glaze, mix it evenly, spray it on the body, and then burn it at high temperature. This can easily lead to three problems: First, after the antibacterial agent is fired in the glaze, it is coated by the glass phase and cannot release antibacterial ions, resulting in insufficient antibacterial performance or even failure; second, the addition of antibacterial agents affects the original glaze system and requires formula improvement, which will undoubtedly affect the widespread promotion of antibacterial ceramic rock slabs; third, the antibacterial agent is added to the glaze, the usage is large, and the cost is high. Summary of the invention

[0004] The present invention provides a composite antibacterial material and a preparation method, a matte antibacterial ceramic rock plate and a preparation method thereof, so as to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0005] In order to overcome the above technical problems, the present invention first provides a composite antibacterial material for the surface of the glaze layer of matte ceramic rock plate, and the composite antibacterial material includes zinc oxide, aluminum oxide and zinc aluminate. The above composite antibacterial material is prepared by the following steps: treating the activated zinc oxide and activated aluminum oxide at 1000℃-1200℃ (for example, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃) for 10min-15min (for example, 10min, 11min, 12min, 13min, 14min, 15min). According to conventional technical means of those skilled in the art, the activated zinc oxide and activated aluminum oxide can be mixed and dispersed by ball milling (for example, ball milling for 5min), and then the above high temperature treatment is performed.

[0006] In the present invention, active zinc oxide and active aluminum oxide are compounded under high temperature conditions to generate a composite antibacterial material containing zinc spinel. The high proportion of zinc oxide in the composite material can release zinc ions with bactericidal effects under the action of air and water, thereby having good antibacterial properties. Moreover, since the composite antibacterial material has undergone high-temperature treatment to generate a partial zinc spinel structure, it has excellent high-temperature resistance. When sprayed onto the surface of the glaze layer of the ceramic rock plate for co-firing, it can stably exist on the surface of the glaze layer like high-temperature dry particles. Compared with some existing means of solidifying antibacterial components on the surface of the glaze layer, the high-temperature co-firing method adopted by the present invention can ensure that the composite antibacterial material of the present invention is more firm and stable on the surface of the glaze layer, can better exert its antibacterial effect, and can also greatly reduce the use of antibacterial materials, thereby reducing costs. In addition, due to the presence of the zinc spinel structure with stable performance, the composite antibacterial material of the present invention is not easily melted and coated by the glaze layer during the co-firing process on the glaze layer surface, so that it is better fixed on the glaze layer surface, thereby giving full play to the antibacterial properties of zinc oxide in the composite antibacterial material; and the formation of zinc spinel can also improve the wear resistance of the surface of the matte antibacterial ceramic rock plate, reduce the loss of the antibacterial layer caused by wear, thereby further improving the durability of the antibacterial performance.

[0007] Among them, the active alumina used in the present invention is different from calcined alumina, and refers to alumina that has not been calcined at high temperature for a long time, and has a smaller grain size and higher activity; while the alumina that has been calcined at high temperature for a long time, that is, calcined alumina, has a large grain size and a crystal form of corundum α crystal with more stable performance. The active zinc oxide used in the present invention is also different from calcined zinc oxide, and refers to zinc oxide that has not been calcined at high temperature for a long time, and has a smaller grain size and higher activity, while the zinc oxide that has been calcined at high temperature for a long time, that is, calcined zinc oxide, has a large grain size and a crystal form of hexagonal zincite with more stable performance.

[0008] If calcined alumina and calcined zinc oxide are used in the technical solution of the present invention, they cannot quickly form a zinc spinel structure with stable performance during high-temperature treatment due to their high crystallinity and stable performance, that is, the composite antibacterial material provided by the present invention cannot be obtained; and when they are subsequently sprayed as antibacterial materials onto the surface of the glaze layer of the matte ceramic rock slab for co-firing, the calcined zinc oxide without a composite structure will react with the glaze and be covered by the glaze layer, thereby causing technical problems such as pinhole defects on the surface of the matte ceramic rock slab and further reduction of antibacterial performance, and the calcined zinc oxide participates more in the reaction of the glaze during the co-firing process, which also increases the glossiness of the glaze; in addition, calcined alumina will also participate too much in the reaction of the glaze, resulting in a milky and whitening problem.

[0009] It is well known that the activated alumina, calcined alumina, activated zinc oxide and calcined zinc oxide mentioned in the present invention are all technical classification concepts known in the art.

[0010] In some preferred embodiments, the mass proportion of activated alumina used in the above-mentioned composite antibacterial material is 5%-20%. For example, it can be 5%, 10%, 15%, and 20%. The present invention uses activated alumina on the one hand to be able to combine with activated zinc oxide under high temperature conditions to form a zinc spinel structure, thereby improving the high temperature stability of the composite antibacterial material and avoiding a large amount of composite antibacterial material being melted and coated by the glaze layer; on the other hand, a small part of alumina can also participate in the reaction of the glass phase of the glaze layer to reduce the gloss of the glaze surface and prevent the problem of a sharp increase in the gloss of the glaze surface due to the addition of zinc oxide. If the mass proportion of activated alumina is higher than the upper limit of the above-mentioned preferred range, too much alumina may participate in the firing process of the glaze, which may make the glaze surface opaque and white, and will cause the zinc oxide to account for a small proportion, affecting the overall antibacterial effect of the composite antibacterial material; if the mass proportion of activated alumina is lower than the lower limit of the above-mentioned preferred range, there may be too much active zinc oxide, and the active zinc oxide will play a great role in fluxing on the surface of the glaze layer, so that the melting point of the attached glaze surface is reduced, and pinhole defects may appear on the surface of the rock plate.

[0011] In some preferred embodiments, the particle size of the active zinc oxide in the above-mentioned composite antibacterial material is 50nm-100nm, for example, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm; the active zinc oxide below 100nm is used mainly because it has a larger specific surface area and higher activity, and if it is lower than 50nm, the cost will be higher; the particle size of the activated alumina is 0.5μm-2μm, for example, 0.5μm, 1μm, 1.5μm, 2μm; if the particle size of the activated alumina is too large, that is, more than 2μm (the particle size of alumina in conventional glazes is 5μm-10μm), then its specific gravity is large and it is easier to settle, which is not conducive to the spraying uniformity of the composite antibacterial material, and if it is lower than 0.5μm, the cost will be higher.

[0012] Based on the above-mentioned composite antibacterial material, the present invention also provides a matte antibacterial ceramic rock plate, which comprises a rock plate blank, a glaze layer and an antibacterial layer in sequence, and the antibacterial layer can be formed by the above-mentioned composite antibacterial material. In some preferred embodiments, the matte antibacterial ceramic rock plate comprises a rock plate blank, a bottom glaze layer, a pattern layer, a protective glaze layer, and an antibacterial layer formed by the above-mentioned composite antibacterial material in sequence.

[0013] The present invention also provides a method for preparing the above-mentioned matte antibacterial ceramic rock slab, comprising the following steps: spraying glaze slurry on the surface of the blank and then drying to obtain a matte ceramic rock slab pretreated blank, then spraying a composite antibacterial slurry on the surface of the matte ceramic rock slab pretreated blank (i.e. spraying it on the glaze surface), drying and then firing to obtain the above-mentioned matte antibacterial ceramic rock slab; the composite antibacterial slurry is obtained by mixing the above-mentioned composite antibacterial material with water and ball milling.

[0014] In some preferred embodiments, the matte surface ceramic rock plate pre-treated body is obtained by the following steps: applying the base glaze slurry, inkjet printing the pattern layer and spraying the protective glaze slurry on the body surface in sequence, and drying to obtain the matte surface ceramic rock plate pre-treated body. Those skilled in the art can also make conventional adjustments to each layer according to actual needs.

[0015] In some preferred embodiments, the ball milling time of the composite antibacterial slurry is 15min-30min, such as 15min, 20min, 25min, 30min; the D50 of the composite antibacterial slurry is 1μm-5μm, such as 1μm, 2μm, 3μm, 4μm, 5μm. In some preferred embodiments, the composite antibacterial slurry further includes a dispersant, such as sodium hexametaphosphate, and its addition amount can be preferably 2%-5% of the mass of the composite antibacterial material, such as 2%, 3%, 4%, 5%.

[0016] In some preferred embodiments, the specific gravity of the composite antibacterial slurry is 1.03 g / mL-1.06 g / mL, for example, 1.03 g / mL, 1.04 g / mL, 1.05 g / mL, 1.06 g / mL. When spraying the matte ceramic rock plate pre-treated body, the spraying amount of the composite antibacterial slurry is preferably 50 g / m 2 -100 g / m 2 , for example 50g / m 2 , 60g / m 2 , 70g / m 2 , 80g / m 2 , 90g / m 2 , 100g / m 2 . If the spraying amount is higher than the upper limit of the above-mentioned preferred spraying amount range, there may be too much zinc oxide content, and part of the zinc oxide participates in the reaction of the glaze, playing a fluxing role, causing pinhole defects on the surface of the rock plate, and also improving the surface gloss; if the spraying amount is lower than the lower limit of the above-mentioned preferred spraying range, it may result in insufficient zinc oxide content, reducing the antibacterial effect.

[0017] In some preferred embodiments, the firing temperature in the above preparation method is 1180°C-1200°C, such as 1180°C, 1190°C, 1200°C, and the firing time is 50min-70min, such as 50min, 55min, 60min, 65min, 70min. Those skilled in the art can perform conventional further treatment as needed, such as grinding the matte antibacterial ceramic rock plate after firing in the above preparation method.

[0018] The beneficial effects of the present invention are as follows: the present invention obtains a composite antibacterial material that has excellent antibacterial properties and can remain stable at high temperatures by high-temperature treatment of active zinc oxide and active aluminum oxide; it can be more firmly and stably present on the surface of the glaze layer of the matte ceramic rock plate through spraying-co-firing, without affecting the matte effect, and while better exerting the effect of the antibacterial material, the amount of the antibacterial material used is greatly reduced, the cost is reduced, and it is suitable for large-scale production and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Shown are XRD spectra of the matte ceramic rock plates prepared in Example 1 and Comparative Example 7;

[0020] Figure 2 Shown are the XRD spectra of the matte ceramic rock panels prepared in Examples 1-3 and Comparative Examples 1-7 within the range of 2θ=36°-37°. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments and drawings to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other without conflict. The same reference numerals used throughout the drawings indicate the same or similar parts.

[0022] The protective glaze used in the following embodiments and comparative examples comprises, by weight percentage, SiO2 (47%-52%), Al2O3 (18%-20%), Fe2O3 (0.3%-0.4%), TiO2 (0.12%-0.15%), CaO (12%-14%), MgO (1%-2%), K2O (1.2%-1.6%), Na2O (3%-4%) and loss on ignition (≤5%).

[0023] Example 1

[0024] A method for preparing a matte antibacterial ceramic rock plate comprises the following steps:

[0025] 1) Prepare a composite antibacterial material; take 95 parts of active zinc oxide and 5 parts of active aluminum oxide, mix them and disperse them by ball milling. After ball milling for 5 minutes, place the mixed powder in an electric furnace for firing at 1050°C for 15 minutes to obtain a composite antibacterial material.

[0026] 2) Prepare a composite antibacterial slurry; mix 21 parts of the above-mentioned composite antibacterial material, 1 part of dispersant sodium hexametaphosphate and 78 parts of water, and then ball mill for 30 minutes. The slurry particle size D50 is 2.3 μm. Then add water to dilute the slurry to a specific gravity of 1.03 g / mL to obtain a composite antibacterial slurry.

[0027] 3) Prepare a matte surface ceramic rock slab pretreatment body; the raw material powder is pressed and formed and then dried to obtain a body, and then the base glaze layer slurry is applied, the pattern layer is inkjet printed and the protective glaze slurry is sprayed on the surface of the body in sequence, and the matte surface ceramic rock slab pretreatment body is obtained after drying.

[0028] 4) Preparation of matte antibacterial ceramic rock board; spray the composite antibacterial slurry obtained in step 2) on the surface of the matte rock board pre-treated body obtained in step 3), with a spraying amount of 100g / m 2 After drying, it is transferred to a roller kiln for firing at a temperature of 1180°C and a firing cycle of 70 minutes. After leaving the kiln, the edges are ground and trimmed to produce a matte antibacterial ceramic rock slab.

[0029] Example 2

[0030] A method for preparing a matte antibacterial ceramic rock plate comprises the following steps:

[0031] 1) Prepare a composite antibacterial material; take 90 parts of active zinc oxide and 10 parts of active aluminum oxide, mix them and disperse them by ball milling. After ball milling for 5 minutes, place the mixed powder in an electric furnace for firing at 1100° C. for 13 minutes to obtain a composite antibacterial material.

[0032] 2) Prepare a composite antibacterial slurry; mix 20 parts of the above-mentioned composite antibacterial material, 0.6 parts of dispersant sodium hexametaphosphate and 79.4 parts of water, and then ball mill for 20 minutes. The slurry particle size D50 is 3.2 μm. Then add water to dilute the slurry to a specific gravity of 1.04 g / mL to obtain a composite antibacterial slurry.

[0033] 3) Prepare a matte surface ceramic rock slab pretreatment body; the raw material powder is pressed and formed and then dried to obtain a body, and then the base glaze layer slurry is applied, the pattern layer is inkjet printed and the protective glaze slurry is sprayed on the surface of the body in sequence, and the matte surface ceramic rock slab pretreatment body is obtained after drying.

[0034] 4) Preparation of matte antibacterial ceramic rock board; spray the composite antibacterial slurry obtained in step 2) on the surface of the matte ceramic rock board pre-treated body obtained in step 3), with a spraying amount of 80g / m 2 After drying, it is transferred to a roller kiln for firing at a temperature of 1190°C and a firing cycle of 60 minutes. After leaving the kiln, the edges are ground and trimmed to produce a matte antibacterial ceramic rock slab.

[0035] Example 3

[0036] A method for preparing a matte antibacterial ceramic rock plate comprises the following steps:

[0037] 1) Prepare a composite antibacterial material; take 80 parts of active zinc oxide and 20 parts of active aluminum oxide, mix them and disperse them by ball milling. After ball milling for 5 minutes, place the mixed powder in an electric furnace for firing at 1200° C. for 10 minutes to obtain a composite antibacterial material.

[0038] 2) Prepare a composite antibacterial slurry; mix 20 parts of the above composite antibacterial material, 0.8 parts of dispersant sodium hexametaphosphate and 79.2 parts of water, and then ball mill for 15 minutes. The slurry particle size D50 is 4.8 μm. Then add water to dilute the slurry to a specific gravity of 1.05 g / mL to obtain a composite antibacterial slurry.

[0039] 3) Prepare a matte surface ceramic rock slab pretreatment body; the raw material powder is pressed and formed and then dried to obtain a body, and then the base glaze layer slurry is applied, the pattern layer is inkjet printed and the protective glaze slurry is sprayed on the surface of the body in sequence, and the matte surface ceramic rock slab pretreatment body is obtained after drying.

[0040] 4) Preparation of matte antibacterial ceramic rock board; spray the composite antibacterial slurry obtained in step 2) on the surface of the matte ceramic rock board pre-treated body obtained in step 3), with a spraying amount of 60g / m 2 After drying, it is transferred to a roller kiln for firing at a temperature of 1200°C and a firing cycle of 50 minutes. After leaving the kiln, the edges are ground and trimmed to produce a matte antibacterial ceramic rock slab.

[0041] Comparative Example 1

[0042] This comparative example 1 provides a method for preparing a ceramic rock board. Compared with the method for preparing a matte antibacterial ceramic rock board in Example 1, the amounts of active zinc oxide and active aluminum oxide added in the process of preparing the composite antibacterial material in this comparative example 1 are 99 parts and 1 part respectively, and the other steps are the same as those in Example 1.

[0043] Comparative Example 2

[0044] This comparative example 2 provides a method for preparing a ceramic rock board. Compared with the method for preparing the matte antibacterial ceramic rock board in Example 1, the amounts of active zinc oxide and active aluminum oxide added in the process of preparing the composite antibacterial material in this comparative example 2 are 70 parts and 30 parts respectively, and the other steps are the same as those in Example 1.

[0045] Comparative Example 3

[0046] This comparative example 3 provides a method for preparing a ceramic rock board. Compared with the method for preparing a matte antibacterial ceramic rock board in Example 1, in this comparative example 3, during the preparation of the composite antibacterial slurry, the active zinc oxide and the active aluminum oxide are ball-milled and mixed without high-temperature sintering and are directly used to prepare the composite antibacterial slurry. The other steps are the same as those in Example 1.

[0047] Comparative Example 4

[0048] This comparative example 4 provides a method for preparing a ceramic rock board. Compared with the method for preparing a matte antibacterial ceramic rock board in Example 1, in the process of preparing the matte antibacterial ceramic rock board in this comparative example 4, the spraying amount of the composite antibacterial slurry is increased to 200 g / m 2 , the other steps are the same as those in Example 1.

[0049] Comparative Example 5

[0050] This comparative example 5 provides a method for preparing a ceramic rock board. Compared with the method for preparing a matte antibacterial ceramic rock board in Example 1, in the process of preparing a matte antibacterial ceramic rock board in this comparative example 5, the spraying amount of the composite antibacterial slurry is reduced to 20 g / m 2 , the other steps are the same as those in Example 1.

[0051] Comparative Example 6

[0052] This comparative example 6 provides a preparation method of a ceramic rock board. Compared with the preparation method of the matte antibacterial ceramic rock board in Example 1, this comparative example 6 replaces the active zinc oxide and the active aluminum oxide with calcined zinc oxide and calcined aluminum oxide respectively in the process of preparing the composite antibacterial material, and the other steps are the same as Example 1.

[0053] Comparative Example 7

[0054] This comparative example 7 provides a method for preparing a ceramic rock slab. Compared with the method for preparing a matte antibacterial ceramic rock slab in Example 1, this comparative example 7 directly performs post-firing on the pretreated blank for preparing the matte ceramic rock slab obtained in step 3) without undergoing a process of spraying a composite antibacterial slurry, thereby obtaining a matte ceramic rock slab.

[0055] Experimental Example 1

[0056] The matte ceramic rock plates prepared in the above Examples 1-3 and Comparative Examples 1-7 were subjected to XRD qualitative testing and found that the XRD spectra of Example 1 and Comparative Example 7 were compared. Figure 1 As shown, the XRD spectra of the two are very similar, but it is obvious that in the range of 2θ of 36°-37°, an obvious crystallization peak appears in the XRD spectrum of Example 1, while the curve at this position in the spectrum of Comparative Example 7 is almost flat. The XRD software analysis shows that the peak at this position is the characteristic peak of the zinc spinel structure (36.7°, ZnAl2O4). Therefore, the XRD spectrum analysis of each embodiment and comparative example can focus on the range of 2θ of 36°-37°, as shown in FIG. Figure 2As shown, Examples 1-3 all have obvious characteristic peaks of zinc spinel structure in the range of 2θ of 36°-37°, and the peak areas of the three gradually increase at this position, as shown in Table 1, which are 42.44, 45.36 and 52.09 respectively (the peak area data described in the scheme of the present invention are all based on the peak area of ​​the blank sample of the matte surface rock board of the same series (i.e., Comparative Example 7) at the characteristic peak position, and the test parameters are: 0.013° / step, 15s / step. It should be noted that the XRD spectrum of the matte surface antibacterial rock board prepared by the present invention is The peak area (integrated intensity) at the position of 36-37° zinc spinel (the strongest peak of the physical phase) is in the range of 40-60 (as shown in Examples 1-3). The range of the peak area is measured under the specific test parameter settings marked. If the parameter data changes, its value will also change accordingly), indicating that the increase of the aluminum oxide content in the composite antibacterial material can increase the proportion of the zinc spinel structure in the composite material; in the spectrum of Comparative Example 1, a characteristic peak of the zinc spinel structure appears in the range of 2θ of 36°-37°, which is slightly lower than that of Example 1, mainly because Because the aluminum oxide content in Comparative Example 1 is reduced; in the spectrum of Comparative Example 2, a characteristic peak of zinc spinel structure appears in the range of 2θ of 36°-37°, and the peak area is significantly increased compared with that of Example 1, which is 159.32, mainly because the aluminum oxide content in Comparative Example 2 is higher; in the spectrum of Comparative Example 3, a characteristic peak of zinc spinel structure appears in the range of 2θ of 36°-37°, and the peak area is slightly lower than that of Example 1, mainly because the active zinc oxide and the active aluminum oxide in Comparative Example 3 have not been pretreated at high temperature, resulting in partial separation of zinc oxide and aluminum oxide. The galvanneal structure reacts with the protective glaze, thereby reducing the proportion of the galvanneal structure. In the spectrum of Comparative Example 4, a characteristic peak of the galvanneal structure appears in the range of 2θ of 36°-37°. Compared with Example 1, the peak area is significantly increased (198.24) and is the strongest peak in all spectral lines. This is mainly because the spraying amount of the composite antibacterial slurry in Comparative Example 4 is significantly increased, which directly leads to the highest content of the galvanneal structure on the surface of the ceramic rock plate. In the spectrum of Comparative Example 5, no obvious characteristic peak of the galvanneal structure is found in the range of 2θ of 36°-37°, and the peak area is as small as 2.07, mainly because the spraying amount of the composite antibacterial slurry in comparative example 5 is low, resulting in the zinc spinel structure on the surface of the ceramic rock plate being too low to be clearly detected; in the spectrum of comparative example 6, a characteristic peak of the zinc spinel structure appears in the range of 2θ of 36°-37°, which is much smaller than the peak area of ​​Example 1, mainly because the zinc oxide and aluminum oxide used in comparative example 6 are calcined zinc oxide and calcined aluminum oxide, and the performance of these two materials is relatively stable. The zinc spinel structure with stable performance cannot be quickly formed during the high-temperature pretreatment process; in the spectrum of comparative example 7, no characteristic peak of the zinc spinel structure is found in the range of 2θ of 36°-37°, mainly because comparative example 7 does not use a composite antibacterial slurry, resulting in the characteristic peak signal of zinc spinel being almost undetectable on the surface of the ceramic rock plate, and the peak area is the lowest and is set to 0 in the scheme of the present invention. Through the above analysis, it can be seen that in the scheme of the present invention, when the amount of active zinc oxide and active aluminum oxide used is determined, the peak area of ​​the prepared matte antibacterial ceramic rock plate at the position of the characteristic peak of zinc spinel is in the range of 40-60. .

[0057] Table 1 Comparison of peak area data at the position of characteristic peaks of zinc spinel in each embodiment and comparative example

[0058]

[0059]

[0060] Experimental Example 2

[0061] Appearance tests were performed on the ceramic tiles prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-7, and it was found that only Examples 1-3, Comparative Example 5 and Comparative Example 7 finally obtained matte ceramic rock slabs with no obvious defects on the surface, and the statistical results are shown in Table 2. Specifically, the matte ceramic rock slab prepared in Comparative Example 1 had obvious pinhole defects on the surface, mainly because the proportion of zinc oxide in the composite antibacterial agent was too large, causing part of the zinc oxide to act as a flux on the surface of the glaze layer, which lowered the melting point of the nearby glaze surface and made the surface of the rock slab prone to pinhole defects; the matte ceramic rock slab prepared in Comparative Example 2 was obviously whitish, mainly because the proportion of aluminum oxide in the composite antibacterial agent was too large, causing too much aluminum oxide to participate in the firing process of the protective glaze, making the glaze opaque and white; the matte ceramic rock slab prepared in Comparative Example 3 had pinhole defects on the surface, mainly because the active zinc oxide and the active aluminum oxide in the composite antibacterial material that was not pretreated at high temperature did not form a zinc spinel structure with stable performance, causing zinc oxide to directly participate in the firing process of the protective glaze as a flux. In the process, the melting point of the nearby glaze is reduced, and pinhole defects are prone to appear on the surface of the rock board; the matte ceramic rock board prepared in Example 4 has more pinhole defects on the surface, mainly because the amount of composite antibacterial slurry sprayed is too much, resulting in a relatively high zinc oxide content and a large amount of participation in the reaction in the protective glaze layer, which plays a fluxing role in the protective glaze, resulting in a large number of pinhole defects on the surface of the rock board; the matte ceramic rock board prepared in Example 6 has obvious pinhole defects on the surface, mainly because the calcined zinc oxide and calcined aluminum oxide have high crystallinity and stable performance. The two cannot quickly form a zinc spinel structure during the high-temperature pretreatment process of the present invention, resulting in zinc oxide and aluminum oxide reacting with the protective glaze layer respectively during the later sintering of the rock board, thereby making the surface of the rock board prone to pinhole defects.

[0062] Experimental Example 3

[0063] The glossiness of the ceramic rock slabs prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-7 was tested, and the data are shown in Table 2. The matte ceramic rock slab prepared in Comparative Example 7 has a minimum average glossiness of 6.0 because no zinc oxide antibacterial agent is added. The average glossiness of the matte ceramic rock slabs prepared in Examples 1-3 and Comparative Examples 1-2 are 6.5, 6.4, 6.3, 7.0 and 6.2, respectively, indicating that the addition of the composite antibacterial material in the examples will lead to an increase in glossiness, and the greater the proportion of zinc oxide in the composite antibacterial material, the higher the glossiness of the matte ceramic rock slab prepared; the glossiness of Comparative Example 3 is increased by 0.4 relative to that of Example 1, mainly because the zinc oxide in Comparative Example 3 is more involved in the reaction of the aluminum oxide without being compounded with the aluminum oxide in advance. The glossiness of the matte ceramic rock board obtained in Example 4 is 11.5, which is almost twice the glossiness of Example 1. This indicates that excessive spraying of antibacterial material slurry will cause a dramatic change in the glossiness of the matte ceramic rock board surface, seriously affecting the appearance of the ceramic rock board product. The glossiness of Example 5 is 6.1, which is mainly due to the small amount of antibacterial material slurry sprayed, which has little effect on the glossiness of the matte ceramic rock board surface. The glossiness of Example 6 is 6.8, which is mainly due to the difficulty of compounding between calcined zinc oxide and calcined aluminum oxide. The zinc oxide participates more in the reaction of the protective glaze during the firing process of the rock board, thereby increasing the glossiness of the glaze.

[0064] Experimental Example 4

[0065] Antibacterial testing: This experimental example is an antibacterial test experiment for the matte ceramic rock slabs of Examples 1-3 and Comparative Examples 1-7 described in the present invention. The antibacterial performance and antibacterial durability of the matte ceramic rock slabs are determined according to the test method of "JC / T 897-2014 Antibacterial Performance of Antibacterial Ceramic Products". The tested bacteria are Staphylococcus aureus and Escherichia coli. The judgment criteria are that the antibacterial performance is greater than or equal to 90% and the antibacterial durability is greater than or equal to 85%. The test results are shown in Table 2.

[0066] The antibacterial performance and antibacterial durability data of Examples 1-3 are all greater than 90%, indicating that the matte antibacterial ceramic rock board prepared by the scheme of the present invention has good antibacterial performance. The antibacterial performance and antibacterial durability data of Comparative Example 1 are all greater than 90%, mainly because the zinc oxide content in its composite antibacterial material is sufficient to produce a large number of antibacterial zinc ions, but due to the insufficient aluminum oxide content, the prepared glaze is prone to produce more pinhole defects; three indicators in the antibacterial performance data of the matte ceramic rock board prepared in Comparative Example 2 are not up to standard, indicating that the proportion of aluminum oxide in the composite antibacterial material will significantly affect its antibacterial performance; the antibacterial performance data of the matte ceramic rock board prepared in Comparative Example 3 are all greater than 90%, but pinhole defects appear on the glaze, mainly because the composite antibacterial material has not been pretreated at high temperature, so that the aluminum oxide and zinc oxide therein react with the glaze respectively. Although the antibacterial performance is good, the glaze is prone to pinhole defects; the antibacterial performance and antibacterial durability data of the matte ceramic rock board prepared in Comparative Example 4 are both greater than 99.99%, but the glaze has more pinhole defects. The above results show that excessive spraying of the composite antibacterial slurry will cause the zinc oxide in the composite antibacterial material to react with the protective glaze, increasing glaze defects; the antibacterial performance and antibacterial durability data of the matte ceramic rock board prepared in Example 5 are both lower than 85%, mainly because the amount of composite antibacterial slurry sprayed in the scheme is insufficient, resulting in the inability to release sufficient antibacterial zinc ions; the antibacterial performance and antibacterial durability data of the matte ceramic rock board prepared in Example 6 show that the antibacterial performance and antibacterial durability against Staphylococcus aureus are lower than 90% and 85% respectively, and the antibacterial performance is unqualified, mainly because calcined alumina and calcined zinc oxide are used in the composite antibacterial material, both of which have stable properties and are difficult to release antibacterial zinc ions. In addition, the two cannot be quickly compounded to form a more stable zinc spinel composite structure during the high-temperature pretreatment process. Therefore, in the later firing process, alumina and zinc oxide respectively participate in the reaction of the protective glaze layer and are covered by the glaze layer, further reducing its antibacterial performance; Comparative Example 7 does not show antibacterial performance, mainly because the scheme does not use composite antibacterial materials.

[0067] Table 2 Comparison of test performance of various embodiments and comparative examples

[0068]

[0069]

[0070] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. A composite antibacterial material for the glaze surface of matte ceramic rock slabs, characterized in that: The composite antibacterial material comprises zinc oxide, aluminum oxide and zinc aluminate.

2. A method for preparing the composite antibacterial material according to claim 1, characterized in that: The method comprises the following steps: treating active zinc oxide and active aluminum oxide at 1000-1200° C. for 10-15 minutes.

3. The preparation method according to claim 2, characterized in that: The mass proportion of activated alumina is 5%-20%.

4. The preparation method according to claim 2 or 3, characterized in that: The particle size of the activated zinc oxide is 50 nm-100 nm; and / or the particle size of the activated aluminum oxide is 0.5 μm-2 μm.

5. A matte antibacterial ceramic rock board, characterized in that: It comprises a rock slab body, a glaze layer and an antibacterial layer in sequence, wherein the antibacterial layer is formed by the composite antibacterial material according to claim 1 or the composite antibacterial material prepared by the preparation method according to any one of claims 2 to 4.

6. The matte antibacterial ceramic rock board according to claim 5 is characterized in that: It includes a rock slab body, a base glaze layer, a pattern layer, a protective glaze layer and the antibacterial layer in sequence.

7. A method for preparing a matte antibacterial ceramic rock plate, characterized in that: The following steps are involved: The glaze slurry is sprayed on the surface of the blank and then dried to obtain a matte surface ceramic rock slab pre-treated blank, and then the composite antibacterial slurry is sprayed on the surface of the matte surface ceramic rock slab pre-treated blank, and then dried and fired to obtain the matte surface antibacterial ceramic rock slab; The preparation method of the composite antibacterial slurry comprises the following steps: mixing the composite antibacterial material according to claim 1 or the composite antibacterial material prepared by the preparation method according to any one of claims 2 to 4 with water and subjecting the mixture to ball milling.

8. The preparation method according to claim 7, characterized in that: The base glaze layer slurry is applied, the pattern layer is inkjet printed, and the protective glaze slurry is sprayed on the surface of the body in sequence, and the matte surface ceramic rock slab pretreated body is obtained after drying.

9. The preparation method according to claim 7 or 8, characterized in that: The ball milling time of the composite antibacterial slurry is 15min-30min; and / or, the D50 of the composite antibacterial slurry is 1μm-5μm; and / or, the composite antibacterial slurry also includes a dispersant; and / or, the specific gravity of the composite antibacterial slurry is 1.03g / mL-1.06g / mL, and the spraying amount of the composite antibacterial slurry is 50g / m 2 -100 g / m 2 .

10. The preparation method according to claim 7 or 8, characterized in that: The firing temperature is 1180℃-1200℃, and the firing time is 50min-70min.